PERANAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK MEMBACA AL QUR’AN - Yuliana Agustin; Shobihus Surur (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to describe the role of parents in increasing children's motivation to read the Qur'an at TPQ Al-Huda, Munggut Hamlet, Cupak Village, Ngusikan District, Jombang Regency. The background of this study is the importance of the role of the family, especially parents, in the formation of children's character and religiosity from an early age, especially in remote areas with limited access to religious education. The research method used is a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that parents have three main roles, namely as motivators, facilitators, and mentors. Children who receive intensive support from their parents show high motivation in learning, such as being diligent in assignments, persistent in facing difficulties, and a spirit of achievement. Supporting factors for children's learning motivation include family support, a conducive learning environment, and the active role of teachers. Meanwhile, inhibiting factors include fatigue due to full-day school, the influence of gadgets, and lack of guidance due to parents' busyness. These findings emphasize the importance of synergy between families and educational institutions in shaping children's religious character.